Impact of Power Factor on the Advancement of Equipment and Technology (International Journal of Innovative Research in Engineering & Management, 2021)
Power electronics equipment and high-voltage systems have  become increasingly common, introducing additional  harmonics into the grid. Harmonic contamination must be  reduced, and transmission performance must be improved,  which necessitates power factor adjustment. A number of  methods have been proposed for power factor adjustment. The  technique of utilizing a Programmable Interface Circuit chip  to build the power factor corrector of a 3-phase power system  was described and planned in this article. Sensors and a  programmable interface circuit detect and measure the load's  power factor value. The information is moved to an algorithm,  which subsequently triggers capacitors based on the  algorithm'sperformance. The capacitor also turns on the lag  and lead power factors, which are shown on an oscilloscope  LCD panel. This will assist to compensate for voltage  regulation and contributes to a power factor that is closer to  unity, thus enhancing the performance of the power system.
Keywords: Capacitor Banks; Oscilloscope; PIC Microcontroller; Power Factor; Pulse Width Modulation; Real Power; Reactive Power